2022
DOI: 10.1021/acsomega.1c06418
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Evaporation on the Inhibition of Spontaneous Coal Combustion

Abstract: Spontaneous coal combustion is the primary cause of coal mine fires. During the production process, spontaneous coal combustion in the goaf is often affected by air leakage, which weakens or annuls the effect of inhibitors and leads to secondary oxidation. However, the action mechanism of inhibitors on secondary oxidation spontaneous coal combustion remains unclear. Thus, this study analyzes the influence of moisture evaporation on the performance of a high-water-content physical inhibitor (HWPI) using the Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Once these materials are injected into the goaf, the moisture in the materials frequently starts to evaporate at the low-temperature stage of the coal due to air leakage of the goaf. The anti-extinguishing efficacy significantly diminished and even disappeared ineffectively after the protracted process of low-temperature oxidation and heating. Thus, it is crucial to search for new and effective mining anti-fire extinguishing materials. Such materials should be able to continuously maintain good fluidity and fire-extinguishing activity in the low-temperature region of coal, gradually undergo a phase change, and weaken fluidity in the high-temperature region of coal, which causes them to gather in the high-temperature region, achieving the effective prevention and control of spontaneous combustion fires in the goaf and getting a multiplier effect.…”
Section: Introductionmentioning
confidence: 99%
“…Once these materials are injected into the goaf, the moisture in the materials frequently starts to evaporate at the low-temperature stage of the coal due to air leakage of the goaf. The anti-extinguishing efficacy significantly diminished and even disappeared ineffectively after the protracted process of low-temperature oxidation and heating. Thus, it is crucial to search for new and effective mining anti-fire extinguishing materials. Such materials should be able to continuously maintain good fluidity and fire-extinguishing activity in the low-temperature region of coal, gradually undergo a phase change, and weaken fluidity in the high-temperature region of coal, which causes them to gather in the high-temperature region, achieving the effective prevention and control of spontaneous combustion fires in the goaf and getting a multiplier effect.…”
Section: Introductionmentioning
confidence: 99%
“…The combustion in the process of modifying activated carbon is related to the properties of activated carbon, solvent properties of modified chemicals, drying gas, drying temperature and time, atmosphere flow, fluidization, and dust and moisture emissions in the drying process. Spontaneous combustion of activated carbon generally occurs when its surface undergoes an exothermic reaction due to oxidation . Onifade’s study indicated that the spontaneous combustion of coal and coal-derived activated carbons is the results of carbon oxidation .…”
Section: Introductionmentioning
confidence: 99%